THE IMPACT OF SMILE APPEARANCE AND SELF-PERCEIVED SMILE ATTRACTIVENESS ON PSYCHOLOGICAL WELL-BEING AMONGST DENTAL UNDERGRADUATES - Sipiyaruk K. (2023)
Introduction: Smile attractiveness can be considered based on tooth alignment, size and shape of teeth, upper lip position, color of teeth, and gingival display. Not only clinical appearance of smile itself but also how it is perceived may impact psychological well-being. Dental students tend to have comprehensive knowledge on dental appearance, which may increase awareness of their smiles. This study aimed to study smile appearance, self-perceived smile attractiveness, and psychological well-being amongst second and sixth year dental students at the Faculty of Dentistry, Mahidol University. Methods: A clinical survey was performed to gather information of smile appearance, and a questionnaire was constructed to collect data regarding self-perceived smile attractiveness and smile-related psychological well-being. The data were analyzed using descriptive data analysis, Spearman correlation, linear regression analysis, and quantitative content analysis. Results: The participants consisted of 85 second year and 40 sixth year dental students. The findings showed significant correlation between smile appearance and self-perceived smile analysis of tooth-related factors in the sixth year students, but that of the second year group found no significant correlation. Self-perceived smile attractiveness of tooth-related and soft tissue-related factors could significantly influence smile-related psychological well-being, but other factors including clinical appearance were not found to be significant predictors. Conclusion: Knowledge and experiences could affect how dental students perceived their smile. In addition, self-perceived smile attractiveness, rather than clinical appearance, seemed to have impact on smile-related psychological well-being.